Oestrus behaviour, follicular growth and ovulation time in cows biostimulated by bulls - Nguyen, Phuc Khanh (2011)
Pheromonal communication plays an important role in animal behaviour and reproductive processes; biostimulation is a kind of pheromonal transmitting information, coined to express the stimulatory effect of a male on a female’s oestrus and ovulation. The biostimulation technique offers a potentially useful and practical way to improve reproductive efficiency in cattle breeding. Therefore, the study was carried out to depict the effects of biostimulation by exposing cows to bulls on oestrus behaviour, follicular growth, and ovulation time. The experiment was conducted on 42 KK cows biostimulated by 3 KK bulls. The cows were divided into three groups: primiparous (PB) and multiparous cows (MB) with bulls and multiparous cows without bulls (CWB). Before start of the research, pregnancy status of the cows was checked through ultrasonography and then, the selected non-pregnant cows were synchronized with CIDR. The cows in each group were housed in three separate paddocks, approximately 1 kilometre away from each other. On the third day of CIDR treatment, 3 bulls were firstly mixed with the cows in the MB group and then, secondly in the PB group. In the CWB group, AI was performed 12 hours after cows had displayed standing heat. Signs of oestrus were observed and scored based on the scoring system developed by Van Eerdenburg et al. (2002). After CIDR removal, follicle growth and ovulation time were determined by scanning the ovaries twice a day for 4 consecutive days. Blood samples were collected 16 times during 45 days for determining plasma progesterone concentration. Pregnancy status of the cows was also checked by ultrasonography on the 35th day from CIDR removal. The overall means percentage of cows in oestrus of the three groups was 90.52% with no significant difference among the groups. However, PB and MB groups scored higher (P<0.05) in signs of oestrus points for intensity of oestrus than CWB. Three main signs commonly displayed by majority of the cows were mounting another cow, being mounted but not standing and standing heat. Cows in the PB and MB groups displayed being mounted but not standing and mounting another cow significantly (P<0.05) more intense than CWB group. However, standing heat exhibited by oestrus cows was not significantly different among the three groups. PB group (23.64±4.15 hours) had significantly longer (P<0.05) duration of oestrus when compared with MB (12.69±2.36 hours) and CWB (13.40±1.50 hours) groups, respectively. In this study, the proportion of ovulation was quite high (90% to 95%) but not significantly different between groups. Ovulation occurred in PB cows significantly longer (P<0.05) than CWB cows from onset of being mounted but not standing and onset of mounting. However, there was no difference in ovulation time from standing heat between groups. No significant difference was also observed in growth of follicle and average daily growth rate in each group. However, dominant follicle size was smaller in PB cows than MB cows. Progesterone concentrations were very low (around 0.7 ng/ml) on day 10 until day 12 in all groups. In PB cows, progesterone concentrations still remained at low levels until day 15. However, it increased slowly in MB and CWB cows. Conception rate in PB and MB groups was significantly higher than CWB group (66.67% and 69.23% vs 23.53%, P<0.05). In conclusion, biostimulation prolonged the duration of oestrus, increased the intensity of oestrus, a number of cows expressed being mounted but not standing and the frequency of cows displayed mounting behaviour in primiparous cows. However, duration of oestrus, intensity of oestrus, growth of follicle, dominant follicle size and ovulation time were not influenced by biostimulation in multiparous cows. Higher conception rate occurred in natural mating than AI.